Frontal midline theta rhythm and gamma activity measured by sheet-type wearable EEG device - Ueno, Keita; Ishii, Ryouhei; Ueda, Masaya; Yuri, Takuma; Shiroma, China; Hata, Masahiro; Naito, Yasuo (Frontiers in Human Neuroscience, 2023)
The current study measured the frontal midline theta rhythm (Fmθ), which appears in the frontal midline region during the attentional focus state, using the sheet-type wearable electroencephalograph (EEG) device HARU-1, and examined the characteristics of other frequency bands. We measured the frontal EEG of 20 healthy subjects using HARU-1 for 2 min during the rest eyes-closed condition and simple mental calculation task condition, respectively. Statistical analyses were conducted using permutation testing based on t-test and cluster analysis to compare the results between the resting state and the task condition. Twelve of 20 subjects showed Fmθ during the task condition. The 12 subjects with Fmθ showed significantly higher activity of the theta and gamma bands, and significantly low activity of the alpha band during the task condition compared to the resting condition. In the 8 subjects without Fmθ were significantly low activity of the alpha and beta bands and no significantly low activity in the theta and gamma band activity during the task condition compared to the resting condition. These results indicate that it is possible to measure Fmθ using HARU-1. As a novel finding, we found gamma band activity in the left and right frontal forehead regions that appeared with Fmθ.